Success, Disabilities, and Adult Education: A Historical Journey - Hether M. Nash; Kara Thrasher-Livingston (Adult Education Research Conference, 2008)
Through historical analysis, adult education is shown to perpetuate widespread social practices of oppression for learners who experience intellectual and other disabilities. A redefinition of whom and what makes a valuable contribution to society is offered; a shift to more inclusive thinking is recommended and a practical necessity due to recent federal legislation.
Keywords: disability; history; education